Operational supply risk and mitigation strategy for halal food manufacturers in Malaysia - Azmi, Fadhlur Rahim (2023)
The globalisation of halal products leads to the vulnerability of the supply chain. Once the halal food supply chain has been breached, it is difficult to rebuild brands and regain consumer trust. Thus, the objective of the study is to investigate operational supply risk management for halal food manufacturers in Malaysia. This study obtained 369 respondents who participated in the main survey by utilising simple random sampling. Then, the dataset was tested using covariance-based software (AMOS) to determine factors of operational supply risk and mitigation strategy and test the hypotheses of the study. This study has revealed that quality, delivery, price and cost are defined as factors of operational supply risks. Meanwhile, behaviour-based management, buffer-based management, and traceability-based management are defined as factors of risk mitigation strategies. Further, this study revealed that halal food manufacturers proactively managed operational supply risks caused by the supplier. Moreover, behaviour-based management and buffer-based management mediate (reducing the effects of operational supply risks) the relationship between operational supply risks and risk consequences. This study significantly contributes to the theoretical knowledge by model development of operational supply risk management for halal food manufacturers, the implication of agency theory, a valid measurement instrument for operational supply risk management for halal food manufacturers, and methodological contribution. Furthermore, from a managerial perspective, the firms may identify the types of risk and their consequences at the supply level, and the firms may implement the appropriate mitigation strategy to manage operational supply risks.